THE INFLUENCE OF ENGLISH MOVIE IN IMPROVING STUDENTS’ SPEAKING SKILL - Halawa, Vanessa Pritin Angel; Sihombing, Melodi Indah; Nasution, Farah Tasya Zafirah (Transpublika Publisher, 2022)
This research was conducted to find out the relationship between English movie and students’ speaking skill. The purpose of this research is to investigate the influence of English movie in improving students’ speaking skill. In this research, researchers used a quantitative approach by implementing experimental research. In its implementation, researchers carried out pre-test and post test to collect data through the value obtained by students. In addition, to strengthening the results of the research, researchers collected data by distributing questionnaires with Likert scale to add quantitative data in this research. The sample in this research were 30 students from class IX-11b in SMP Negeri 2 Pematangsiantar. Based on the results of the research, researchers can conclude that English movie has good impacts and has good influences in improving students’ speaking skills. Keywords : English movie, Speaking skill, Students